2016
DOI: 10.1186/s40478-016-0298-3
|View full text |Cite
|
Sign up to set email alerts
|

High expression of α-synuclein in damaged mitochondria with PLA2G6 dysfunction

Abstract: To clarify the role of α-synuclein (αSyn) in neuronal membrane remodeling, we analyzed the expression of αSyn in neurons with a dysfunction of PLA2G6, which is indispensable for membrane remodeling. αSyn/phosphorylated-αSyn (PαSyn) distribution and neurodegeneration were quantitatively estimated in PLA2G6-knockout (KO) mice, which demonstrate marked mitochondrial membrane degeneration. We also assessed the relationship between αSyn deposits and mitochondria in brain tissue from patients with PLA2G6-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…In PLA2G6 knockout mice, abnormal mitochondria with multiple morphological changes are presented in the anterior horns spinal cord [ 107 ]. Most interestingly, in PLA2G6 knockout mice as well as PLA2G6 knockdown cells, α-syn levels are increased [ 108 ]. The immunoreactivity of S129-site phosphorylated α-syn is strongly presented in neuronal granules which are labeled with mitochondrial outer membrane 20 kDa protein (TOM20) in PLA2G6 knockout mice [ 108 ], suggesting an accumulation of α-syn on damaged mitochondria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PLA2G6 knockout mice, abnormal mitochondria with multiple morphological changes are presented in the anterior horns spinal cord [ 107 ]. Most interestingly, in PLA2G6 knockout mice as well as PLA2G6 knockdown cells, α-syn levels are increased [ 108 ]. The immunoreactivity of S129-site phosphorylated α-syn is strongly presented in neuronal granules which are labeled with mitochondrial outer membrane 20 kDa protein (TOM20) in PLA2G6 knockout mice [ 108 ], suggesting an accumulation of α-syn on damaged mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Most interestingly, in PLA2G6 knockout mice as well as PLA2G6 knockdown cells, α-syn levels are increased [ 108 ]. The immunoreactivity of S129-site phosphorylated α-syn is strongly presented in neuronal granules which are labeled with mitochondrial outer membrane 20 kDa protein (TOM20) in PLA2G6 knockout mice [ 108 ], suggesting an accumulation of α-syn on damaged mitochondria. In PLAN brains, α-syn labeled small inclusions are colocalized with TOM20, which may develop to LBs [ 108 ], further suggesting a role of PLA2G6 in mitochondrial dysfunction and LB formation.…”
Section: Introductionmentioning
confidence: 99%
“…In iPLA 2 β-null mice decreased brain docoshexaenoic acid metabolism and signaling have been observed that may play a role in neuronal dysfunction 58,59 . It has also been suggested that neuroaxonal dystrophy in iPLA 2 β deficiency results from insufficient remodeling and degeneration of mitochondrial and presynaptic membranes 60 , and there is evidence of mitochondrial injury and dysfunction in iPLA 2 β-null mice 61,62 and of increased mitochondrial lipid peroxidation and dysfunction in brains of iPLA 2 β-null Drosophila and in fibroblasts of human subjects with iPLA 2 β gene mutations that cause INAD 63 . iPLA 2 β PARK14 mutants are also defective in preventing rotenone-induced mitochondrial dysfunction, generation of reactive oxygen species, and activation of the mitochondrial apoptotic pathway under conditions where WT iPLA 2 β does prevent these events 64 .…”
Section: Ipla 2 β: the Beginningmentioning
confidence: 99%
“…Although the pathological mechanism of PLA2G6 remains elusive, it has been suggested to affect lipid homeostasis and metabolism as well as impact mitochondrial membranes ( Beck et al, 2011 ). Further, PLA2G6 knockout mice displayed degenerated mitochondrial membranes and elevated levels of synuclein ( Sumi-Akamaru et al, 2016 ). PLA2G6 has been reported to be immunopositive in the Lewy bodies of idiopathic PD, suggesting its pathogenic role extends beyond familial PD ( Miki et al, 2017 ).…”
Section: Genetic Mutations In Pdmentioning
confidence: 99%